2010
DOI: 10.1523/jneurosci.1551-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

SNARE Force Synchronizes Synaptic Vesicle Fusion and Controls the Kinetics of Quantal Synaptic Transmission

Abstract: Neuronal communication relies on rapid and discrete intercellular signaling but neither the molecular mechanisms of the exocytotic machinery that define the timing of the action potential-evoked response nor those controlling the kinetics of transmitter release from single synaptic vesicles are known. Here, we investigate how interference with the putative force transduction between the complexforming SNARE (soluble N-ethylamide-sensitive factor attachment protein receptor) domain and the transmembrane anchor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 67 publications
5
49
1
Order By: Relevance
“…To study the nature of release activity in the absence of syb2 we grew murine hippocampal neurons from syb2 KO (Schoch et al 2001) and WT littermates on glial microislands and performed whole cell patch-clamp experiments on autaptic neurons. Consistent with previous findings (Guzman et al 2010), excitatory evoked release was virtually absent in the KO group (Fig. 1).…”
Section: Resultssupporting
confidence: 92%
“…To study the nature of release activity in the absence of syb2 we grew murine hippocampal neurons from syb2 KO (Schoch et al 2001) and WT littermates on glial microislands and performed whole cell patch-clamp experiments on autaptic neurons. Consistent with previous findings (Guzman et al 2010), excitatory evoked release was virtually absent in the KO group (Fig. 1).…”
Section: Resultssupporting
confidence: 92%
“…However, an earlier as well as a recent study have shown that overexpression of N-or C-terminal GFP fusion constructs of syb2 in syb2-deficient hippocampal neurons fully rescues the amplitude and kinetics of evoked excitatory postsynaptic potentials in syb2-deficient neurons (32,33). SNARE assembly is believed to generate sufficient energy to drive membrane fusion (4,6,7).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, deletion of syb2 alone, the predominant syb isoform in SVs, was shown to result in a 10-fold reduction of spontaneous fusion and a 100-fold decrease in fast Ca 2+ -triggered exocytosis in hippocampal synapses (31), thus providing a clean loss-of-function background for rescue experiments. Indeed, expression of syb2 fused to fluorescent proteins at the luminal domain in KO neurons was previously shown to rescue evoked exocytosis (32,33). Here, we first tested the ability of spH to rescue synaptic function in these hippocampal synapses (Fig.…”
Section: +mentioning
confidence: 99%
“…Hippocampal neurons were isolated as described previously 38 . Chromaffin cells were isolated as described previously 39,40 .…”
Section: Methodsmentioning
confidence: 99%
“…The methods used for electrophysiological recordings of hippocampal neurons 38,41 and chromaffin cells 40,42 were previously described.…”
Section: Methodsmentioning
confidence: 99%